Research of PNPLA3 I148M Gene Polymorphism in Patients with Non-Alcoholic Fatty Liver Disease, with Liver Cirrhosis and with Hepatocellular Carcinoma - V. V. Petkau; G. A. Tsaur; E. N. Bessonova; A. A. Karimova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Aim: to determine the frequency of PNPLA3 rs738409 C>G gene polymorphism, leading to p.I148M substitution, in patients with non-alcoholic fatty liver disease (NAFLD), and to reveal the association between polymorphism and probable NAFLD outcomes: liver cirrhosis (LC) and hepatocellular carcinoma (HCC).Materials and methods. The study was conducted according to the “case-control” design, three main groups were formed: a group with NAFLD (n = 46), a group with LC (n = 61), a group with HCC (n = 50), as well as a control group (n = 70), for all groups we performed genotyping of the rs738409 polymorphism of the PNPLA3 gene. The relationship between the occurrence of different genotype variants and the diagnosis of patients was evaluated, the odds ratio (OR) of progression of NAFLD and the reliability of intergroup differences were determined.Results. NAFLD patients with PNPLA3 I148M polymorphism have a significantly higher chance of developing LC and HCC. The odds ratio for the GG genotype was 7.94 (95 % Cl: 2.19–28.84; p = 0.030) for LC and 6.51 (95 % Cl: 1.15–4.08; p = 0.039) — for HCC with concomitant LC. The presence of the minor G allele also increases the likelhood of transition from NAFLD to LC (OR = 2.38; 95 % Cl: 1.41–4.02; p = 0.010) and HCC in the presence of cirrhosis (OR = 2.17; 95 % Cl: 1.15–4.08; p = 0.039). Differences in the frequency of PNPLA3 polymorphism between the NAFLD and HCC groups were not significant. Additional risk factors for HCC associated with NAFLD are overweight (OR = 5.14; 95 % Cl: 1.94–13.67; p < 0.001), arterial hypertension (OR = 8.49; 95 % Cl: 3.05–23,62; p < 0.001) and diabetes mellitus (OR = 8.57; 95 % Cl: 1.03–71.48; p = 0.032).Conclusion. The frequency of single nucleotide polymorphism PNPLA3 significantly differs in patients with NAFLD, cirrhosis and HCC compared with the control group of healthy volunteers. The PNPLA3 I148M polymorphism increases the incidence of NAFLD progression to cirrhosis and HCC, but only with concomitant cirrhosis.